Effective recruitment sourcing methods towards employment outcomes in Malaysia marine and heavy engineering - Ahmad Zaini, Muhammad Zaki (2012)
Employment outcomes is a hiring success of organization needed to run company production towards organization goals. If company can identify effective sourcing methods to hiring success employment outcomes, company can increase their productivity and so, will increase the company sales. This research was conducted to determine the relationship between sourcing methods (advertisements, headhunters, and career fairs) with employment outcomes. The main objective is to identify the most influential sourcing method towards employment outcomes. This research was investigated in a sample of 132 employees by using questionnaires. Result showed that the most influential method is advertisements. Recommendations for future research also has been discussed.